Helen Keller : courage in the dark - Hurwitz, Johanna (New York : Random House, 1997)
A biography of the blind and deaf girl who overcame both handicaps with the help of her teacher, Annie Sullivan.
"Grades 2-3"--Cover.
Keywords: Keller, Helen, -- 1880-1968 -- Juvenile literature; Sullivan, Annie, -- 1866-1936 -- Juvenile literature; Keller, Helen, -- 1880-1968.; Sullivan, Annie, -- 1866-1936.; Deafblind women -- United States -- Biography -- Juvenile literature; Blind; Deaf; People with disabilities; Women -- Biography